BrainFit: improving executive and subjective cognitive functioning in late-life mood disorders - a double-blind randomized active-controlled study evaluating the effect of online cognitive training - Oudega, Mardien L.; Wagenmakers, Margot J.; Palsma, Tanya; Hoogendoorn, Adriaan W.; Vriend, Chris; van den Heuvel, Odile A.; Schouws, Sigfried; Dols, Annemiek (Frontiers in Psychiatry, 2025)
IntroductionUnipolar and bipolar mood disorders in older adults are accompanied by cognitive impairment, including executive dysfunction, with a severe impact on daily life. Up and till now, strategies to improve cognitive functioning in late-life mood disorders (LLMD) are sparse. Therefore, we aimed to assess the efficacy of adaptive, computerized cognitive training (CT) on executive and subjective cognitive functioning in LLMD.MethodsIn this double-blind, randomized controlled study we enrolled patients over the age of 50 with partly remitted LLMD. Over 8 weeks, patients participated in 24 45-minute sessions of computerized multi-domain training (CT) or an active control condition (ACC) (nonspecific cognitive activity). The primary outcome was executive functioning based on the interference score on the STROOP task (not incorporated in the training). Secondary outcomes were subjective cognitive functioning, depressive symptoms and quality of life. Outcomes were assessed before and after training (T1) and at a 3-month follow-up (T2) and analyzed with linear mixed-model analyses.ResultsThirty-eight patients were included in the study, 22 in the experimental CT and 16 in the ACC. Mean age was 67.3 years and 52.6% was female. Linear mixed-model analyses showed small within-group effect sizes, corresponding to no statistically significant improvement of executive functioning or depression severity in either group. In both groups we did observe an improvement on subjective cognitive functioning over time. From T0 to T1 the mean score of the Cognitive Functioning Questionnaire (CFQ) of the CT group decreased from 52.7 to 46.8 points (p=0.003) and the mean CFQ score of the ACC group decreased from 52.7 to 45.7 points (p<0.001). This effect remained in both groups at follow-up (T2); respectively p=0.002 and p<0.001.The patients in the AAC also showed an improvement of quality of life directly after the training (T1); i.e. the mean quality of life scores improved from 53 to 57 points (p=0.011), but this effect did not remain at follow-up.ConclusionsThis study shows no beneficial effect of an 8-week computerized CT on the primary outcome, i.e, executive functioning. Subjective cognitive functioning did improve in both groups, indicating that frequent cognitive training is advantageous. Future studies with more intensive training could be designed to explore this result further.Clinical trial registrationclinicaltrials.gov, identifier NCT04006756.